1992
DOI: 10.1159/000247447
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Peripheral Blood Eosinophil Counts in Severe Psoriatic Patients Treated with Low-Dose Cyclosporine A

Abstract: We report a clinical observation, a statistically significant decrease in peripheral blood eosinophils in patients treated with low-dose cyclosporine A for severe psoriasis 225/μl at baseline to 114/μl at week 12 (p = 0.04). We discuss the potential significance of this clinical finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Calcineurin inhibitors such as ciclosporin have previously been shown to inhibit histamine release from basophils and mast cells when stimulated with anti‐IgE antibodies and pimecrolimus (ascomycin) seemed to be more potent than ciclosporin [14]. They also have inhibitory effects on other important components of the inflammatory/immune response, most notably T lymphocytes [16], and also eosinophils [17]. Basophils are dependent on T cell derived IL‐3 for priming, although IL‐3 levels of sera and supernatants tested were not determined.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin inhibitors such as ciclosporin have previously been shown to inhibit histamine release from basophils and mast cells when stimulated with anti‐IgE antibodies and pimecrolimus (ascomycin) seemed to be more potent than ciclosporin [14]. They also have inhibitory effects on other important components of the inflammatory/immune response, most notably T lymphocytes [16], and also eosinophils [17]. Basophils are dependent on T cell derived IL‐3 for priming, although IL‐3 levels of sera and supernatants tested were not determined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is strongly suggested that there may be a relationship between cytokines, especially IL-5, and eosinophils in patients with allergic rhinitis. Moreover, CyA decreases peripheral blood eosinophils in severe psoriatic patients [30]. Although species difference must be considered, these results suggest that CyA may inhibit antigen-induced hypersensitivity also in patients with allergic rhinitis.…”
Section: Discussionmentioning
confidence: 74%
“…There are reports showing a significant and rapid decrease in peripheral blood eosinophil counts in psoriatic patients treated with cyclosporine 8,9 . A recent report of a case with psoriasis vulgaris, who showed peripheral blood eosinophilia paralleling PASI scores, provided a further evidence for the role of eosinophils in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 92%
“…7 There are reports showing a significant and rapid decrease in peripheral blood eosinophil counts in psoriatic patients treated with cyclosporine. 8,9 A recent report of a case with psoriasis vulgaris, who showed peripheral blood eosinophilia paralleling PASI scores, provided a further evidence for the role of eosinophils in the pathogenesis of psoriasis. The patient described in this report was treated with tacalcitol ointment, indicating that treatment modalities seems to be less important in lowering the blood eosinophil counts, instead, the improvement of psoriasis is directly related with this laboratory result.…”
Section: Discussionmentioning
confidence: 93%